(3OjhGf JGL Gdedhcs - (3eLO GdOjf CHhSYjO HhQj Hf CjhH Hf TGPj Hf eQhGf,J (B579 (3g` s
(3ChdgG (B:s
(3ef bGajI GdgeRI Ndb Gdghi OGA HZjQ OhGA aYdjdg CHOkG HZjQ TaGA s
(3BNQgG (B:s
(3ef bGajI GdjGA hEfi dCSJTai ef GdHjf HGdQhi hMSHc OGkA Cf JQi GdehJ TGajkG s
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi bhGais
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B56s
Keywords: (3GdCOHs